Frequency of Thrombocytopenia and ICU Mortality in Patients with Sepsis - Aftab, Hamza; Beg, Atif; Mazhar, Kanwal (Biological and Clinical Sciences Research Journal, 2025)
Thrombocytopenia is a common hematological abnormality in sepsis and may serve as a predictor of adverse outcomes. Objective: This study aimed to determine the frequency of thrombocytopenia in septic patients and assess its association with ICU mortality. Methods: This cross-sectional study was conducted at the Department of Medicine, PAEC General Hospital, Islamabad from October 2024 till March 2025. A total of 90 septic patients admitted to the ICU were enrolled using a non-probability consecutive sampling technique. Platelet counts were recorded on admission and on day 7. Thrombocytopenia was defined as a platelet count <150,000/µL. Mortality during the ICU stay was recorded. Results: The mean age of patients was 54.3 ± 12.7 years, with 55.6% males. Thrombocytopenia was present in 36 patients (40%). Overall ICU mortality was 31.1%, with a significantly higher mortality rate in thrombocytopenic patients (47.2%) compared to non-thrombocytopenic patients (20.4%) (p = 0.007). A downward trend in platelet count from admission to day 7 was observed. Stratified analysis showed significantly higher mortality in patients aged ≥60 years (p = 0.041), while diabetes mellitus and chronic hepatitis C did not significantly affect mortality. Conclusion: It is concluded that thrombocytopenia is significantly associated with increased ICU mortality in septic patients and may serve as a reliable prognostic marker. Monitoring platelet trends during ICU stay can assist in early identification of high-risk patients and guide clinical management.